Robust and Sustainable Indium Anode Leading to Efficient and Stable Organic Solar Cells - Xiang, Jiale; Liu, Zhi‐Xi; Chen, Hongzheng; Li, Chang‐Zhi (Advanced materials (Weinheim), 2023)
The fast degradation of the charge‐extraction interface at indium tin oxide (ITO) poses a significant obstacle to achieving long‐term stability for organic solar cells (OSCs). Herein, a sustainable approach for recycling non‐sustainable indium to construct efficient and stable OSCs and scale‐up modules is developed. It is revealed that the recovered indium chloride (InCl 3 ) from indium oxide waste can be applied as an effective hole‐selective interfacial layer for the ITO electrode (noted as InCl 3 –ITO anode) through simple aqueous fabrication, facilitating not only energy level alignment to photoactive blends but also mitigating parasitic absorption and charge recombination losses of the corresponding OSCs. As a result, OSCs and modules consisting of InCl 3 –ITO anodes achieve remarkable power conversion efficiencies (PCEs) of 18.92% and 15.20% (active area of 18.73 cm 2 ), respectively. More importantly, the InCl 3 –ITO anode can significantly extend the thermal stability of derived OSCs, with an extrapolated T 80 lifetime of ≈10 000 h.